Impact of Physical Activity on Symptoms and Quality of Life in Women with Endometriosis: A Narrative Review - Chrobak, Agata; Bessmylna , Kateryna; Kravets , Alesia; Zhukava, Lizaveta; Alansi, Abdulrahman; Weng, Kai-Chiun; Żukowska , Joanna (Quality in Sport, 2026)
Background. Endometriosis is an estrogen-dependent inflammatory disease that significantly impairs women’s quality of life through chronic pelvic pain, dysmenorrhea, dyspareunia, infertility, and psychological distress. Increasing attention has been directed toward non-pharmacological approaches, including physical activity. Aim. This review aimed to analyze current evidence on the effects of physical activity and different exercise modalities on symptoms and quality of life in women with endometriosis. Material and methods. A narrative review was conducted using PubMed, Scopus, and Web of Science, focusing on studies published between 2020 and 2026, including randomized controlled trials, systematic reviews, and observational studies. Results. Available evidence suggests that physical activity may reduce pain, improve quality of life, enhance mental well-being, and improve physical functioning. The most beneficial effects are associated with combined interventions including aerobic exercise, resistance training, and mind–body techniques. Conclusions. Physical activity may be an effective complementary strategy in the management of endometriosis; however, further high-quality studies are needed.